Evaluation of chemical composition and inhibition potential of fusel oil against different microorganisms (Research, Society and Development, 2020)
The control of contamination in the fermentation process is essential to ensure productivity. To minimize the load of contaminants, acid treatment and the addition of antibiotics are carried out. However, in the ethanol production process itself, other alcohols are formed that result in a mixture known as fusel oil that can be used to minimize contamination. Thus, this study aims to analyze fusel oil samples, characterize and evaluate the inhibition potential of this substance against different microorganisms. Initially, a bibliographic survey was carried out to identify the biomass and understand the stages of formation of fusel oil. Concomitantly, samples of fusel oil were analyzed with respect to physical-chemical parameters and chemical composition. The inhibition potential of fusel oil was evaluated with the inhibition halo test using the yeasts Catanduva-1 (Cat-1) and FT-858 and the bacteria Salmonella tiffi (ATCC 14028), Escherichia coli (ATCC 25922), Stafilicoccus aureus (ATCC 25923) and Bacillus sp. The production of fusel oil is directly related to yeast metabolism. The samples showed differences in physical-chemical parameters and both had a high content of isoamyl alcohol. The bacteria showed sensitivity to fusel oil demonstrating that this by-product can be used as an antiseptic and antibacterial agent.